ANTINOCICEPTIVE EFFECT OF D-ASPARTIC ACID IN MICE - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1995)
The effects of D- and L-aspartic acids on the nociceptive tail flick reflex in mice were investigated. D-Aspartic acid (115-230 mg/kg, IF) was found to increase tail flick latency significantly. Naloxone (0.1 mg/kg) abolished the analgesic effect of D-aspartic acid (115 mg/kg). Morphine and D-aspartic acid, when combined at their nonanalgesic doses, led to significant analgesia. It may be concluded that the opioid system is involved in the antinociceptive effect of D-aspartic acid. Both morphine and D-aspartic acid were previously reported to inhibit L-aspartic acid production via blockade of L-asparaginase. L-Aspartic acid, which was ineffective alone, significantly inhibited the antinociceptive effects of both D-aspartic acid and morphine.
Keywords: ASPARTIC ACID; ANALGESIA; MORPHINE; NALOXONE; RAT SPINAL-CORD; AMINO-ACIDS; DORSAL HORN; MORPHINE-DEPENDENCE; KETAMINE ANALGESIA; NMDA RECEPTORS; NALOXONE; GLUTAMATE; NEURONS; NEUROTRANSMISSION